Β‐Adrenergic blockade does not impair the skin blood flow sensitivity to local heating in burned and nonburned skin under neutral and hot environments in children. (May 2017) - Rivas, Eric; McEntire, Serina J.; Herndon, David N.; Mlcak, Ronald P.; Suman, Oscar E.
ABSTRACT: Objective: We tested the hypothesis that propranolol, a drug given to burn patients to reduce hypermetabolism/cardiac stress, may inhibit heat dissipation by changing the sensitivity of skin blood flow (SkBF) to local heating under neutral and hot conditions. Methods: In a randomized double‐blind study, a placebo was given to eight burned children, while propranolol was given to 13 burned children with similar characteristics (mean±SD: 11.9±3 years, 147±20 cm, 45±23 kg, 56±12% Total body surface area burned). Nonburned children (n=13, 11.4±3 years, 152±15 cm, 52±13 kg) served as healthy controls. A progressive local heating protocol characterized SkBF responses in burned and unburned skin and nonburned control skin under the two environmental conditions (23 and 34°C) via laser Doppler flowmetry. Results: Resting SkBF was greater in burned and unburned skin compared to the nonburned control (main effect: skin, P <.0001; 57±32 burned; 38±36 unburned vs 9±8 control %SkBFmax ). No difference was found for maximal SkBF capacity to local heating between groups. Additionally, dose‐response curves for the sensitivity of SkBF to local heating were not different among burned or unburned skin, and nonburned control skin (EC50, P >.05) under either condition. Conclusion: Therapeutic propranolol does not negatively affect SkBF under neutral or hot environmental conditions and further compromise temperature regulation in burned children.